The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s00436-019-06220-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of propidium monoazide–based qPCR to detect viable oocysts of Toxoplasma gondii

Abstract: Information on the viability of Toxoplasma gondii oocysts is crucial to establish the public health significance of this environmental transmission stage that can contaminate water and foods. Interest for molecular-based methods to assess viability is growing and the aim of our study was to assess, for the first time, a propidium monoazide (PMA)-qPCR approach to determine the viability of T. gondii oocysts. Untreated and heat-killed (99°C, 5 min) oocysts were incubated with PMA, a photoreactive DNA binding dye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 56 publications
1
20
0
1
Order By: Relevance
“…However, some studies have shown that the seroprevalence is probably related to seasons [17], and the reason for this difference may be due to different environments, temperatures, and various sample qualities. Moreover, studies have shown that high temperatures have little impact on the reduction in viability of T. gondii [15].…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies have shown that the seroprevalence is probably related to seasons [17], and the reason for this difference may be due to different environments, temperatures, and various sample qualities. Moreover, studies have shown that high temperatures have little impact on the reduction in viability of T. gondii [15].…”
Section: Discussionmentioning
confidence: 99%
“…Only mechanical grinding with TissueLyser (30 s) associated with Lysing Matrix E tube in IMDM growth media achieved the release of 84  14% of sporocysts. However, this percentage of released sporocysts is probably underestimated because 10%-15% of oocysts never sporulate (32). This method can be easily implemented in laboratories and can be applied to oocysts isolated from environmental or food samples as mussels.…”
Section: Discussionmentioning
confidence: 99%
“…Methods to measure the viability and infectivity of protozoa including T. gondii have been recently reviewed (31). Among molecular techniques, Propidium MonoAzide based-PCR assays appeared not relevant to measure the viability of T. gondii oocysts (32) and RNA based-methods overestimated the exposure of humans to viable oocysts because of persistence of RNA in dead parasites (33,34). Considering that all viable parasites are not necessarily infectious, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Four cats excreted T. gondii -like oocysts; however, oocysts infectivity was not reported, and it is not clear if the kittens were tested for T. gondii antibodies before use in the experiment. Recently, methods for detection and viability measure of T. gondii oocysts were described and they could be employed in Egypt in order to determine the contamination of the environment (Rousseau et al ., 2019).…”
Section: Toxoplasmosis In Animalsmentioning
confidence: 99%